2009
DOI: 10.1016/j.bbagrm.2009.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin-targeting protein Brd2 is required for neural tube closure and embryogenesis

Abstract: Chromatin modifications are essential for directing transcription during embryonic development. Bromodomain-containing protein 2 (Brd2; also called RING3 and Fsrg1) is one of four BET (bromodomain and extra terminal domain) family members known to selectively bind acetylated histones H3 and H4. Brd2 associates with multiple subunits of the transcriptional apparatus including the mediator, TFIID and Swi/Snf multi-protein complexes. While molecular interactions of Brd2 are known, the functions of Brd2 in mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 44 publications
2
81
0
Order By: Relevance
“…Our results do not exclude specific roles of Brd2 during the neuronal differentiation program because, as mentioned above, Brd2 protein, besides being detected in neural progenitors in the developing neural tube, also appears in differentiating neurons along the dorsoventral axis, including interneurons, motoneurons and sensory neurons . Although several reports have suggested an involvement of Brd2 in the process of neuronal differentiation (Gyuris et al, 2009;Tsume et al, 2012;Velíšek et al, 2011), specific conditional knockout mice are required to accurately assess this issue. Finally, despite functional redundancy between Ptn and Mdk, an interesting developmental phenotype associated with the single Ptn mutation in mice supports our model: absence of Ptn results in prolonged proliferation and therefore in impaired neurogenesis in the cerebral cortex (Hienola et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results do not exclude specific roles of Brd2 during the neuronal differentiation program because, as mentioned above, Brd2 protein, besides being detected in neural progenitors in the developing neural tube, also appears in differentiating neurons along the dorsoventral axis, including interneurons, motoneurons and sensory neurons . Although several reports have suggested an involvement of Brd2 in the process of neuronal differentiation (Gyuris et al, 2009;Tsume et al, 2012;Velíšek et al, 2011), specific conditional knockout mice are required to accurately assess this issue. Finally, despite functional redundancy between Ptn and Mdk, an interesting developmental phenotype associated with the single Ptn mutation in mice supports our model: absence of Ptn results in prolonged proliferation and therefore in impaired neurogenesis in the cerebral cortex (Hienola et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some BET members have been additionally associated with cell differentiation. In this regard, the family member bromodomain-containing protein 2 (Brd2), besides interacting with the transcription factor E2F and controlling expression of cyclin A2 and D1 in proliferating cells (Belkina et al, 2014;Denis et al, 2000;Garcia-Gutierrez et al, 2012;LeRoy et al, 2008;Sinha et al, 2005), is expressed in differentiating neurons , which might be linked to the neural tube closure defects observed in Brd2-knockout mouse embryos and to the association of mutations in the BRD2 locus with human juvenile myoclonic epilepsy (Gyuris et al, 2009;Shang et al, 2009;Velíšek et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of fs(1)h cause segmental abnormalities, including missing organs and homeotic transformations in the progeny of mutant females in Drosophila (13). Knockout of Brd4 or Brd2 in mice results in early embryonic lethality (18,21).The BET proteins have been shown to be important players in human disease, including viral infections and cancer. Several different viruses target the individual BET proteins for a variety of purposes but often to regulate viral and cellular transcription (4,7,31,37,41,45,57,60).…”
mentioning
confidence: 99%
“…Mutations of fs(1)h cause segmental abnormalities, including missing organs and homeotic transformations in the progeny of mutant females in Drosophila (13). Knockout of Brd4 or Brd2 in mice results in early embryonic lethality (18,21).…”
mentioning
confidence: 99%
“…It remains unclear how BRD2 and BRD3 can substitute for one another and whether BRD3 can functionally replace BRD2 at all genes. While knockout of BRD2 or BRD4 in mice results in early embryonic lethality (Houzelstein et al, 2002;Gyuris et al, 2009;Shang et al, 2009), a BRD3 knockout mouse has not been reported.…”
Section: Brd3 ((Bromodomain Containing 3)mentioning
confidence: 99%